GerPaCyst - The trial protocol of the prospective, multicenter, interdisciplinary German Pancreas Club Cyst Registry - Kim Christin Honselmann; Jonathan Marschner; Anna Staufenbiel; Julia Bertram; Steffen Deichmann; Carsten Engelke; Martha Kirstein; Jens Marquardt; Marko Damm; Fanny Borowitzka; Veit Phillip; Ilaria Pergolini; et al. (PLoS ONE, 2025)
Introduction Cystic lesions of the pancreas have continued to present a clinical challenge for the past decades now. The increasing rate of detection, the lack of high-quality data on the natural biology of pancreatic cysts and the resulting difficulty to predict malignant transformation in different types of pancreatic cysts make patients with these diseases hard to manage. The German Pancreas Club Cyst Registry (GerPaCyst) (DRKS00025927) aims to establish a platform to discover and survey the natural and specific biology of pancreatic cysts such as IPMNs (main and branch ducts), SCNs, SPPT and MCNs, in a multicenter manner. Materials and methods This manuscript is written according to the SPIRIT guidelines (See S2 and S3 Tables). Ethical approval was obtained from the University of Luebeck (2020-20-225) and all participating centers. In GerPaCyst patients aged ≥18 years with a pancreatic cyst under surveillance or scheduled for surgery should be enrolled. Participating centers will complete an electronic Case Report Form (eCRF) via REDCap which is designed as a longitudinal study minimizing the input of repeated measures. Changes in patient baseline data, cyst characteristics, both endoscopic and imaging data will be entered typically every 6–12 months during patient follow-up. Biobanking will be performed, when available. Duration of observation per patient is up to a maximum of 20 years or until end of follow-up or death. Results The primary goal is to assess and calculate individual risk models for malignancy/high-grade dysplasia based on the collected clinical, molecular and imaging data (multi-omics prediction models) for each included cyst entity, therefore the primary outcome of this trial is the development of high-grade dysplasia/invasive cancer during follow-up or the absence of it. The secondary outcomes are death, quality of life measured by EQ-5D-5L questionnaire, end-of-follow up and perioperative characteristics, if applicable such as complications, length of hospital stay and clavien-dindo classification. Another goal will be to build a multicenter, interdisciplinary database to generate high-quality cyst biology data, which can then be used for further research questions. Additionally, this database will be utilized for registry- based interventional trials in the future. Discussion GerPaCyst will provide a valuable platform for clinical outcomes research. Fundamental factors affecting the development of pancreatic cysts over time will be identified. New research questions might be answered during the study period and will be made available through continuous publications. Trial registration The study was prospectively registered at the German Clinical Trial Register (DRKS) under DRKS00025927 on September 14 th , 2021, before inclusion of the first patient. The Universal Trial Number (UTN) is U1111-1302–9822.